Hypovitaminosis D and cardiovascular outcomes: A systematic review and meta-analysis. (June 2022) - Jaiswal, Vikash; Ishak, Angela; Peng Ang, Song; Babu Pokhrel, Nishan; Shama, Nishat; Lnu, Kriti; Susan Varghese, Jeffy; Storozhenko, Tatyana; Ee Chia, Jia; Naz, Sidra; Sharma, Prachi; Jaiswal, Akash
Highlights: Vitamin D deficiency can not only affect bones but have association with cardiovascular effects. The likelihood of unfavorable cardiovascular outcomes, especially major adverse cardiovascular event (MACE), new MI, and all-cause mortality among deficient vitamin D patient is poorly understood. This is a first and most comprehensive meta -analysis with the largest sample size thus far comparing vitamin D levels in terms of cardiovascular outcomes. High risk patients need to monitor vitamins level and implement vitamins supplementation to avoid adverse outcomes especially elder females. Abstract: Background: The relation between blood vitamin D levels and the risk of cardiovascular outcomes is debatable. To our knowledge this is the first comparative meta -analysis of more than 100, 000 patients' data with the aim to inspect the relevance of low vitamin D levels with adverse cardiovascular events. Methods: Online databases including PubMed, Embase and Cochrane Central were queried to compare the cardiovascular outcomes among hypovitaminosis D (HVD) and control group. The outcomes assessed included differences in major adverse cardiovascular events (MACE), mortality, myocardial infarction, and heart failure. Unadjusted odds ratios (OR) were calculated using a random-effect model with a 95% confidence interval (CI) and P less than 0.05 as a statistical significance. Results: A total of 8 studies including 426, 039 patients were included in this analysis. HVD group was associated with a higher incidence of MACE (OR 1.92, 95% CI 1.24 to 2.98, p = 0.003), while there was no significant association of HVD and all-cause mortality (OR 1.77, 95% CI 0.75 to 4.17, p = 0.19), risk of myocardial infarction (OR 0.69, 95% CI 0.39 to 1.24, p = 0.22), and heart failure (OR 1.20, 95% CI 0.34 to 4.25, p = 0.78). Conclusions: This meta -analysis suggested that low blood levels of vitamin D are associated with MACE, but no such difference in all-cause mortality, myocardial infarction or heart failure was observed. Appropriate supplementation of vitamin D in selected populations might be cardioprotective in nature and warrants extensive trials.